Computational rim illumination of dynamic subjects using aerial robots - Srikanth, Manohar; Bala, Kavita; Durand, Frédo (Computers & graphics, 2015)
Lighting plays a major role in photography. Professional photographers use elaborate installations to light their subjects and achieve sophisticated styles. However, lighting moving subjects performing dynamic tasks presents significant challenges and requires expensive manual intervention. A skilled additional assistant might be needed to reposition lights as the subject changes pose or moves, and the extra logistics significantly raises costs and time. The associated latencies as the assistant lights the subject, and the communication required from the photographer to achieve optimum lighting could mean missing a critical shot. We present a new approach to lighting dynamic subjects where an aerial robot equipped with a portable light source lights the subject to automatically achieve a desired lighting effect. We focus on rim lighting, a particularly challenging effect to achieve with dynamic subjects, and allow the photographer to specify a required rim width. Our algorithm processes the images from the photographer׳s camera and provides necessary motion commands to the aerial robot to achieve the desired rim width in the resulting photographs. With an indoor setup, we demonstrate a control approach that localizes the aerial robot with reference to the subject and tracks the subject to achieve the necessary motion. In addition to indoor experiments, we perform open-loop outdoor experiments in a realistic photo-shooting scenario to understand lighting ergonomics. Our proof-of-concept results demonstrate the utility of robots in computational lighting. [Display omitted] •We demonstrate the first approach for studio quality lighting using aerial robots.•Our lighting robot automatically positions itself to produce optimal rim lighting.•Our robot adapts to changes in subject position, subject posture and camera position.•We validate our approach with several indoor experiments.•Using an open-loop outdoor setup, we discuss design issues and ergonomic issues of robotic lighting.